The Principles of Social Education in the Prophet’s Sunnah and its Applications in The School Environment - Alshamrani, Ayman Ahmed (Journal of Educational and Psychological Sciences, 2021)
The study aimed to explain the principles of social education in the Prophet's Sunnah and its applications in the school environment. The study relied on the deductive approach. The study found that social education in Islam was consistent, integrated and inclusive for all members of society. It is an integrated Rabbani approach that is not deficient or defective. The study showed that the Prophet's Sunnah aims at everything that will strengthen the social ties between members of society and be a society characterized by solidarity, togetherness and cooperation and it is common for love, security and stability. The study found that the prophetic principles in social education are all very beautiful and that it is an integrated Islamic curriculum that can be applied at anytime, anywhere and in any educational institution. The school is one of these institutions in which the principles and methods of the Prophet can be applied. In the light of the results, the study recommended providing the curriculum with social topics related to the biography of prophet Muhammad, peace and blessings be upon him, in his dealings with the people, and urged teachers and students to apply them on the ground, and recommended that an office in universities and schools be devoted to caring for Islamic social education, addressing social problems and providing educational advice.
Keywords: Social Education; Prophetic Sunnah; School Environment